Understanding the environmental and herbicide response of Lasiodiplodia theobromae and Bipolaris bicolor isolated from infected Eleusine indica - Fakri, Muhammad Aiman; Sapak, Zaiton; Ahmad Hamdani, Muhammad Saiful; Seng, Chuah Tse (Sociedade Brasileira da Ciencia das Plantas Daninha, 2024)
Background: In a prior study, Lasiodiplodia theobromae (Pat.) Griffiths and Maubl. and Bipolaris bicolor (Mitra) Shoemaker., were found to suppress the growth of Eleusine indica (L.) Gaertn, but limited information exists on their response to environmental factors and herbicides for integrated E. indica control. Objective: This study aimed to determine the tolerance levels of L. theobromae and B. bicolor to pH, temperature, photoperiod, relative humidity, and herbicides. Methods: The mycelia and conidia of L. theobromae and B. bicolor were exposed to a range of environmental conditions and herbicides in a controlled setting, including different levels of temperature (25, 30, 35 ⁰C), pH (4, 6, 8, 10), photoperiod (24 hours of darkness; alternating 12 hours of blue light followed by 12 hours of darkness; and alternating cycles of 6 hours of blue light and 6 hours of darkness), and relative humidity (75, 85, 95%). Herbicides such as topramezone, diuron, oxyfluorfen, and imazethapyr were applied at their recommended rates. Conidial germination was assessed by counting after an 18-hour incubation using a haemocytometer, while the diameter of mycelium growth was measured after 3 days of incubation, except for the herbicide effects evaluation, which were extended over 7 days. Results: Laboratory assays demonstrated that L. theobromae exhibited higher conidial germination of 85-95% and superior mycelial growth under varied pH, temperature, and photoperiod conditions compared to B. bicolor. Lasiodioplodia theobromae’s mycelia remained unaffected by herbicides at full labelled rates, but they inhibited the conidial germination of the fungus. For B. bicolor, the conidia were not affected by imazethapyr and topramezone, but its mycelial growth was reduced by imazethapyr, oxyfluorfen, and diuron. Conclusions: These results indicate that the mycelia of L. theobromae presents a more favorable option for tank mixing with test herbicides, offering potential for the formulation of an integrated control strategy against E. indica.